MATHEMATICAL SELF-EFFICACY OF STUDENTS IN COOPERATIVE LEARNING WITH TWO STAY TWO STRAY TECHNIQUES - Habibullah, Habibullah (Jurnal Pendidikan Matematika Undiksha, 2020)
This research is a classroom action research that aimed to improve the process of learning mathematics in terms of students' self-efficacy through the application of cooperative learning two stay two stray techniques. The subjects of this study were 32 students from one of the junior high schools in the city of Yogyakarta. Data collection techniques were carried out using a self-efficacy questionnaire sheet consisting of 24 favorable and unfavorable statements. The results showed that the application of cooperative learning two stay two stray techniques can improve the learning process and improve students' mathematical self-efficacy. This can be seen from the increase in the average value of student mathematics learning outcomes based on the category of self-efficacy